The impact of Islamic State's ideological correction initiative on al Qaeda's bid for relevance - Turner, John (Routledge Journals, Taylor & Francis Ltd, 2019)
Al Qaeda following 9-11 experienced a period of stagnation which it sought to remedy through a project of re-branding. Critical of this approach, Islamic State claimed that al Qaeda was an elitist organization that had facilitated the stagnation of the Salafi Jihadist project. In an attempted to claim dominance over the jihad, Islamic State's endeavored to discredit al Qaeda through a process it presented as ideological correction, linked to Islamic eschatology, sectarian agitation, permissive violence, and the caliphate. Following Islamic State's acquisition of vast territory in Iraq and Syria, arguments proliferated that Islamic State had surpassed al Qaeda. As the caliphate has collapsed what effects will this have on al Qaeda's fortunes and strategy? It is argued that Islamic State has provided al Qaeda's strategic approach with renewed vigour to help ensure its survival and pursue resurgence. Al Qaeda acting in concert with the meta-strategy for survival concept, has altered an existential threat into an advantage through disavowing Islamic State's methods, continuing to engage with localism, and pursuing rebranding by positioning itself as a moderate alternative. The cases of al Qaeda affiliates in Yemen, Syria, West Africa, and South Asia are instructive in assessing the effectiveness of al Qaeda's resurgence.
Keywords: Al Qaeda; Islamic State; ideology; terrorism; Salafi Jihadism